Physical education and the Sdgs: A Decade of Research Trends Through Bibliometric analysis -2015-2024 - Triansyah, Andika; Hidayat, Yusuf; Lukitowati, Suci (Edukasi, 2025)
This study aims to map scientific trends and global contributions in the field of physical education, sports, and physical activity in relation to the achievement of the Sustainable Development Goals (SDGs) through a bibliometric approach. A total of 393 documents indexed in the Scopus database (2015–2024) were analyzed using VOSviewer software version 1.6.20. The methods applied included co-word analysis to identify key themes, co-authorship analysis to explore collaboration networks, and co-citation analysis to trace the most influential literature. The findings indicate a significant increase in publication output since 2020. Research output is predominantly composed of journal articles (61%), highlighting the prevalence of both empirical and conceptual contributions. In terms of source type, 79% of the documents were published in peer-reviewed scientific journals, indicating strong engagement with reputable academic platforms. Spain emerged as the most productive country, with Baena-Morales, S. as the leading author and Universitat d'Alacant as the most prolific institution. Dominant keywords such as sustainable development goals, physical activity, and humans reflect a growing global focus on integrating physical activity and physical education within the sustainability agenda. This study underscores the need for enhanced multidisciplinary collaboration and increased engagement from developing countries to accelerate the achievement of the SDGs through physical education.